REFLEKSI FILOSOFI TERHADAP PERAN GURU DALAM PENDIDIKAN MORAL ANAK PRA SEKOLAH - Diyasika Ulinafiah (STPI Bina Insan Mulia Yogyakarta, 2024)
Preschool moral education plays a crucial role in shaping a child's character. The teacher, as a key figure, reflects on the ontological, epistemological, and ethical implications of their role. The contextualization of education involves the complexity of understanding human nature, the learning process, and educational objectives. In the ontological dimension, a profound understanding of human morality is essential, and from an epistemological perspective, questions arise regarding the teacher's role as a guide in conveying moral knowledge to preschoolers. The ethical aspects of the teacher's role encompass interactions and responsibilities towards society and the future moral development of children. This conclusion serves as a foundation for further philosophical exploration of the teacher's role in shaping the morality of preschool children, supporting the development of effective and sustainable moral education methods. Keywords: philosophical reflection, teacher's role, moral education, early childhood.